The agency domain and behavioral interactions: assessing positive animal welfare using the Five Domains Model - Littlewood, Katherine E.; Heslop, Morgan V.; Cobb, Mia L. (Frontiers in Veterinary Science, 2023)
Animal welfare denotes how an animal experiences their life. It represents the overall mental experiences of an animal and is a subjective concept that cannot be directly measured. Instead, welfare indicators are used to cautiously infer mental experiences from resource provisions, management factors, and animal-based measures. The Five Domains Model is a holistic and structured framework for collating these indicators and assessing animal welfare.Contemporary approaches to animal welfare management consider how animals can be given opportunities to have positive experiences. However, the uncertainty surrounding positive mental experiences that can be inferred has resulted in risk-averse animal welfare scientists returning to the relative safety of positivism. This has meant that aspects of positive welfare are often referred to as animal 'wants'. Agency is a concept that straddles the positivist-affective divide and represents a way forward for discussions about positive welfare. Agency is the capacity of individual animals to engage in voluntary, self-generated, and goal-directed behaviour that they are motivated to perform. Discrete positive emotions are cautiously inferred from these agentic experiences based on available knowledge about the animal's motivation for engaging in the behaviour. Competence-building agency can be used to evaluate the potential for positive welfare and is represented by the Behavioural Interactions domain of The Five Domains Model.In 2020, The Model was updated to, amongst other things, include consideration of human-animal interactions. The most important aspect of this update was the renaming of Domain 4 from 'Behaviour' to 'Behavioural Interactions' and the additional detail added to allow this domain's purpose to be clearly understood to represent an animal's opportunities to exercise agency. We illustrate how the Behavioural Interactions domain of The Model can be used to assess animals' competence-building agency and positive welfare.In this article, we use the examples of sugar gliders housed in captivity and greyhounds that race to illustrate how the agentic qualities of choice, control, and challenge can be used to assess opportunities for animals to exercise agency and experience positive affective engagement.